Attenuation of cytotoxicity induced by tBHP in H9C2 cells by Bacopa monniera and Bacoside A. Issue 2 (June 2018) - T, Mohan Manu; Anand, T.; Khanum, Farhath
Graphical abstract: Abstract: Cardiovascular diseases are one of the major global health issues leading to morbidity and mortality across the world. In the present study Bacopa monniera and its major bioactive component, Bacoside A (Bac-A) was used to evaluate its cytoprotective property in H9C2 cardiomyocytes against tBHP (150 μM) induced ROS-mediated oxidative stress and apoptosis. Our results implicate that pre-treatment with hydroalcoholic extract of Bacopa monniera (BME) and Bac-A (125 μg/ml and 6 μg/ml respectively) significantly restored oxidative stress by scavenging the free radicals and also elevated phase II antioxidant defensive enzymes such as (SOD, CAT, GR, GPx and GSH). Membrane integrity was estimated by MMP and LDH assays and found 89 and 72% of the protective effect. Further immunoblotting studies confirmed anti-apoptotic effects by regulating protein expression like Bcl2 was up-regulated to 99 and 85% and Bax was down-regulated to 122 and 181%, iNOS by 154.38 and 183.45% compared to tBHP (277.48%) by BME and Bac-A. BME and Bac-A exerts cytoprotective efficacy by attenuation of ROS generated through oxidative stress by an increase in the concentration of antioxidant enzymes and sustain membrane integrity which leads to restoring the damage caused by tBHP.